Gender differences in information behavior during the Covid-19 health crisis in Spain - Michela Montesi (JLIS.it, 2021)
The Covid-19 pandemic has produced numerous deaths throughout the planet, although in general it has been deadlier in older people, in people with previous conditions and in males. The biomedical literature explains the difference in terms of mortality between men and women pointing to genetics and social and cultural reasons. The aim of this work is to explore information behavior, among the other sociocultural variables possibly influencing health outcomes in men and women. For this, we analyze the results of a survey with 95 people administered in Madrid the last week of strict lockdown for Covid-19 (April 2020). Questions were asked about the reasons for using traditional mass media and social media, the use of official and institutional information, the characteristics of the information that was considered useful, and different dimensions of information behavior during lockdown. Results show that the differences between men and women affect certain dimensions of information behavior and especially the information characteristics that are considered useful. Slight differences were also perceived between the two sexes regarding social media, that men appeared to use more for entertainment than communication.